Fratture periprotesiche: la revisione del ginocchio in acuto - Benazzo, F.; Ghiara, M.; Rossi, S.M.P. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FRACTURE—ACUTE KNEE REVISION Periprosthetic fractures are an increasingly common complication following total knee arthroplasty, especially in geriatric patients. Supracondylar fracture is the most frequent type and it is often linked to femoral notching. The correct classification of the fracture prompts the surgical decision; however, the loosening of a prosthetic implant needs revision surgery in the acute setting. The purpose of the treatment includes bone defect reconstruction and the stability of the implant, to allow for immediate weight-bearing and fast patient rehabilitation.